Effects of Pasteurization and High-Pressure Processing of Camel and Bovine Cheese Quality, and Proteolysis Contribution to Camel Cheese Softness - Mbye, Mustapha; Mohamed, Huda; Ramachandran, Tholkappiyan; Hamed, Fathalla; AlHammadi, Ahlam; Kamleh, Rabih; Kamal-Eldin, Afaf (Frontiers in Nutrition, 2021)
The effect of heat pasteurization (65 °C for 30 min and 75 °C for 30 seconds) and high-pressure processing (HPP, 350, 450, and 550 MPa for 5 minutes) on the quality of soft unripened camel and bovine milk cheeses were studied. The cheeses were evaluated for pH, yield, proximate composition, textural and rheological properties, microstructure, and protein profile by SDS-PAGE electrophoresis. Cheeses produced from the high temperature pasteurized milk (75 °C) and the most elevated pressure (550 MPa) had the highest yields, moisture content, lowest hardness and viscosity, and smooth and more homogenized microstructures. Cheeses produced from milk pasteurized at the low temperature (65 °C) and the lowest pressure (350 MPa) had the best textural and rheological properties. HPP (350 MPA) is promising in tremendously improving the quality of camel milk cheese. SDS-PAGE electrophoresis revealed, for the first time, that extensive proteolysis has contributed to the softness of camel cheeses suggesting the involvement of some residual enzyme activities.